Daily use of consensus interferon: One-year treatment results for chronic hepatitis C patients relapsing ornon-responding to previous interferon - Zeki KARASU,; Ahmet GÜRAKAR,; Ahmad JAZZAR,; Harlan WRİGHT, (Turkish Journal of Gastroenterology, 2019)
-